Fingi(dores) de si mesmos: dores fingidas e reais na oratória romana (Nuntius Antiquus, 2014)
This paper focuses on the conceptions of ethos and pathos in Roman rhetoric in order to investigate how far were ancient Romans from our notion of poetical persona. Its title dialogues with the poem “Autopsicografia” by Fernando Pessoa, whose “feigned pain” has a correlate in Ciceronian fictus dolor. This preliminary consideration is part of our broader investigation on the reception of subjective poetry in ancient Rome, and more widely in classical studies.